Greenfield versus merger & acquisition FDI: Same wine, different bottles? - Ronald B. Davies; Rodolphe Desbordes; Anna Ray (University College Dublin, UCD School of Economics, 2015)
Relying on a large foreign direct investment (FDI) transaction level dataset, unique both in terms of disaggregation and time and country coverage, this paper examines patterns in greenfield (GF) versus merger & acquisition (MA) investment. Although both are found to seek out large markets with low international barriers, important differences emerge. MA is more affected by geographic and cultural barriers and exhibits opportunistic behaviours as it is more sensitive to short-run changes, such as a currency crisis. On the other hand, GF is relatively driven by long-run factors, such as origincountry technological and institutional development or comparative advantage. These empirical facts are consistent with the conceptual distinction made between these two modes, i.e. MA involves transfer of ownership for integration or arbitrage reasons while GF relies on firms own capacities, which are linked to the origin countries attributes. They also suggest that GF and MA are likely to respond differently to policies intended to attract FDI.
Keywords: F21; F23; 330; Foreign Direct Investment; Mergers and Acquisitions; Greenfield Investment; Multinational Firms